Real world outcomes with Bortezomib Thalidomide dexamethasone and Cyclophosphamide Bortezomib dexamethasone induction treatment for transplant eligible multiple myeloma patients in a Latin American country. A Retrospective Cohort Study from Grupo Argentino de Mieloma Múltiple. Issue 3 (20th April 2020) - Schütz, Natalia P.; Ochoa, Paola; Duarte, Patricio; Remaggi, Guillermina; Yantorno, Sebastián; Corzo, Ariel; Zabaljauregui, Soledad; Shanley, Claudia; Lopresti, Sergio; Orlando, Sergio; Verri, Verónica; Quiroga, Luis; et al.
Abstract: Data about treatment outcomes and toxicity in Latin America are scarce. There are differences with central countries based on access to healthcare system and socioeconomic status. Argentinean Society of Hematology recommends bortezomib‐based triplets for induction treatment of transplant eligible newly diagnosed multiple myeloma patients. Most common options are CyBorD (cyclophosphamide, bortezomib and dexamethasone) and VTD (bortezomib, thalidomide and dexamethasone). Main goal of our retrospective, multicentric study was to compare very good partial response rate (VGPR) or better after induction treatment in a real‐world setting in Argentina. Secondary objectives included comparison of complete response (CR) post‐induction and after bone marrow transplantation, grade 3‐4 adverse events (AEs), progression‐free survival (PFS) and overall survival (OS). Three hundred twenty‐two patients were included (median age at diagnosis: 57 years; 52% male; 28% had ISS3; 14% with high‐risk cytogenetics; median follow up: 34 months). CyBorD was indicated in 74% and 26% received VTD. In VTD arm, 72.62% of patients achieved at least VGPR vs 53.36% receiving CyBorD (odds ratio, OR: 1.96 [95% confidence interval, CI: 1.08‐3.57; P = .026] after adjusting by age, ISS [International Staging System], lactate dehydrogenase levels (LDH) and cytogenetic risk. Difference in VGPR was 19.26% (95% CI: 15‐24). CR rate were 35.92% (VTD) vs 22.55% (CyBorD) (adjusted OR: 2.13 [95% CI: 1.12‐4.05]). Difference in CR was 13.37% (95% CI: 9.6‐17.53). Adverse events (AEs) were more common with VTD (69.05% vs 55.46% for CyBorD; P = .030), especially grade 3‐4 neuropathy ( P = .005) and thrombosis ( P = .001). Thromboprophylaxis was inadequate in 20.24% of patients. Hematological AEs were more common with CyBorD, especially thrombocytopenia ( P = .017). PFS and OS at 24 months were not different between treatments. In this real‐world setting, VTD was associated with better CR and VGPR than CyBorD. Nevertheless, CyBorD continues to be the preferred induction regimen in Argentina, based on safety profile. Frontline autologous stem cell transplantation improves quality of responses, especially in countries with limited access to new drugs.